(untitled) (Progressive Agriculture, 2021)
The present experiment was carried out at the Laboratories of the Department of Horticulture and Biochemistry and Molecular Biology, Bangladesh Agricultural University, Mymensingh during the period from February to April 2019 to study the effect of maturity indices and modified atmosphere packaging (MAP) on the extension of shelf life and quality retention of cherry tomato. The two-factor experiment consisted of three maturity indices viz. (i) Maturity index 1 (M1: Mature green color), (ii) Maturity index 2 (M2: Yellow color), and (iii) Maturity index 3 (M3: Red color) and five postharvest treatments viz. (i) Control (T0), (ii) Low density perforated poly ethylene, LDPPE (T1), (iii) Low density poly ethylene, LDPE (T2), (iv) Low density perforated plastic box, LDPPB (T3), and (v) Low density plastic box, LDPB (T4). The experiment was conducted in completely randomized design with 3 replications. The maximum weight loss (7.77%) was recorded in mature green color fruits (M2) treated with control (T0), while the minimum (3.22) was found in yellow color fruits (M2) treated with LDPPB (T3). The maximum color change was observed from yellow color fruits (M2) with LDPPB (T3) and the minimum was observed from mature green color fruits (M1) treated with control (T0). The maximum TSS content (7.20%) was recorded from yellow color fruits (M2) treated with LDPB (T4), while the minimum (5.67%) was found in mature green color fruits (M1) treated with LDPPB (T3). The highest disease incidence and severity (16.67% and 21.67%, respectively) were recorded in red color fruits (M3) treated with control whereas the lowest disease incidence (1.67%) and severity (2.33%) were found in yellow color fruits (M2) treated with LDPPB. The longest shelf life (25.00 days) was obtained in yellow color fruits (M2) treated with LDPPB (T3) and the shortest shelf life (7.00 days) was observed in red color fruits (M3) treated with control (T0). Thus, yellow color fruits (M2) treated with LDPPB (T3) could be used for the extension of shelf life and quality retention of cherry tomato. Progressive Agriculture 32 (1): 43-59, 2021